Sylvia Wynter : On Being Human as Praxis - McKittrick, Katherine (Book collections on Project MUSE., 2015)
"The Jamaican writer and cultural theorist Sylvia Wynter is best known for her diverse writings that pull together insights from theories in history, literature, science, and black studies to explore race, the legacy of colonialism, and representations of humanness. Sylvia Wynter: On Being Human as Praxis is a critical genealogy of Wynter's work, highlighting her insights on how race, location, and time together inform what it means to be human. The contributors explore Wynter's stunning reconceptualization of the human in relation to concepts of blackness, modernity, urban space, the Caribbean, science studies, migratory politics, and the interconnectedness of creative and theoretical resistances. The collection includes an extensive conversation between Sylvia Wynter and Katherin McKittrick that delineates Wynter's engagement with writers such as Frantz Fanon, W.E.B. DuBois, and Aime Cesaire, among others; the interview also reveals the ever-extending range and power of Wynter's intellectual project, and elucidates her attempts to rehistoricize humanness as praxis"--Publisher's description.